Cyber security and malware - Okhanashvili, Svimon ("Intercultural Dialogues" Transactions, 2023)
The development of modern technologies contributed to the development of the virtual world - the Internet space, where both private production and service departments, as well as state institutions, went on a work visit. This led to the spread and exchange of huge information in the Internet world, which in turn made it necessary to raise and strengthen the level of cyber security, which today is a necessary and demanding topic. Thesis - Cyber security and malware is one of the most relevant topics today and calls for the detection of various types of cybercrime threats, their types and the implementation of necessary measures. In fact, every day there are high-level threats on the Internet, most of which are related to cyber security, which in turn is one of the main measures, so to speak, of the Internet security policy, which implies: quick active response and action to protect information from various malicious programs and malicious actions. Information threats can be caused both by human factors, such as various types of threats (unintentional, accidental, targeted), and by natural factors: storms, lightning, earthquakes, floods, etc. In general, during cybercrime, attention is focused on: technical, software and organizational part. The software part refers to operating systems and application software shells, most of which are made by different companies and their installation requires a lot of attention in the direction of compatibility and compliance. Technical refers to digital devices and their capabilities, while organizational protection refers to: employee selection, education, distribution, placement in special positions, including the formation and enhancement of cooperation and teamwork, increasing the protection of work ethic, information and behavior requirements.